Diversity of the photoreceptors and spectral opponency in the compound eye of the Golden Birdwing, Troides aeacus formosanus. - Pei-Ju Chen (Public Library of Science (PLoS), 2013)
The compound eye of the Golden Birdwing, Troides aeacus formosanus (Papilionidae, Lepidoptera), is furnished with three types of ommatidia, which are clearly different in pigmentation around the rhabdom. Each ommatidium contains nine photoreceptors, whose spectral sensitivities were analyzed electrophysiologically. We identified nine spectral types of photoreceptor with sensitivities peaking at 360 nm (UV), 390 nm (V), 440 nm (B), 510 nm (BG), 540 nm (sG), 550 nm (dG), 580 nm (O), 610 nm (R), and 630 nm (dR) respectively. The spectral sensitivities of the V, O, R and dR receptors did not match the predicted spectra of any visual pigments, but with the filtering effects of the pigments around the rhabdom, they can be reasonably explained. In some of the receptors, negative-going responses were observed when they were stimulated at certain wavelengths, indicating antagonistic interactions between photoreceptors.